Reasons why Russian is complicated to learn than English - Bazarov Ihtiyor Rahmatullayevich; Kenesova Jazira Bauirjan qizi (Zien Journals, 2022)
The present article lists the main reasons why the russian language is much more challenging in terms of language acquisition than english. It also discusses the specific grammar rules that puzzle the majority of learners
Keywords: Obstacle; Russian; grammar; noun gender